2019
DOI: 10.5858/arpa.2019-0291-ra
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Evaluation of Malignant Polyps and Low-Stage Colorectal Carcinoma

Abstract: Context.— With widespread screening for colorectal cancer, the number of early-stage colorectal cancers is increasing. Local excision of pT1 tumors is associated with considerably less morbidity and mortality, but this must be weighed against risk of lymph node metastases. Objective.— To understand histologic prognostic factors associated with adverse outcome in malignant polyps. Data Sources.— Pertinent literature regarding histologic features of prognostic significance in malignant polyps and low-stage color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Kikuchi et al [ 43 ] proposed a 3-tiered system for sessile polyps, where sm 1, 2, and 3 represent invasion of cancer into the first, second and deepest thirds of the submucosa, respectively. In their study, this system showed a good correlation with lymph node metastatic risk (sm1 0%, sm2 5%, sm3 25%), later confirmed by other authors [ 44 ]. The Kikuchi and Haggitt systems may be difficult to use in clinical practice, since the received sample may be fragmented or suboptimally orientated on histological sections, and because the muscularis propria , needed if the classifications are to be used, is usually not included in local endoscopic excisions [ 11 , 44 ].…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Kikuchi et al [ 43 ] proposed a 3-tiered system for sessile polyps, where sm 1, 2, and 3 represent invasion of cancer into the first, second and deepest thirds of the submucosa, respectively. In their study, this system showed a good correlation with lymph node metastatic risk (sm1 0%, sm2 5%, sm3 25%), later confirmed by other authors [ 44 ]. The Kikuchi and Haggitt systems may be difficult to use in clinical practice, since the received sample may be fragmented or suboptimally orientated on histological sections, and because the muscularis propria , needed if the classifications are to be used, is usually not included in local endoscopic excisions [ 11 , 44 ].…”
Section: Introductionsupporting
confidence: 73%
“…To bypass the limitations, an alternative based on quantitative parameters has been proposed. Ueno et al [ 45 ] suggested the use of the absolute depth of invasion, which can be obtained using an optical micrometer or digital slide software on scanned slides [ 8 , 44 ]. When the invasion depth is <1 mm, it is considered as “superficial SMI”, while an invasion depth of ≥1 mm is classified as “deep SMI”, which has been associated with a considerable risk of residual disease in the bowel wall or lymph nodes after endoscopic resection [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several pathological factors can predict the risk of recurrence and/or LN invasion: resection border (above 1 mm but even 0.1 mm in some studies) [ 3 , 6 , 8 , 18 , 19 , 20 ], depth of invasion [ 3 , 6 , 7 , 21 ] (Table 2 ), pedunculated vs sessile type [ 3 , 6 , 7 , 21 ], differentiation grading (higher risk in G3 grade and in mucinous, signet ring and micropapillary carcinoma) [ 7 , 8 ], lymphovascular invasion [ 1 , 3 , 8 ] and tumoral budding [ 1 , 8 , 22 , 23 ]. LN involvement is very important because in case of resected colorectal T1 SM carcinoma polyps a LN invasion can demand surgical intervention, while cases with no LN involvement can be managed only by local close surveillance [ 1 ].…”
Section: ⧉ Introductionmentioning
confidence: 99%
“…The histological features of complete removal are the presence of normal colonic epithelium on both sides of the tumorous element and in some techniques hyalinised amorphous material at the base of the specimen. [10,11] The above reporting style enables the pathologist to be more accurate in passing important information to the clinician and ultimately to the patient. This work was subsequently confirmed in a more comprehensive study in 2014 where false positive reporting was found in 18.8% of cases when the tumour biopsies were compared to the definitive resection surgery.…”
Section: Adenomatous Polypsmentioning
confidence: 99%